Economia municipal e financiamento de campanhas: uma análise das eleições legislativas municipais de 2008 e 2012 em nove municípios do estado do Rio Grande do Sul - Kwiatkowski, Gustavo Oliveira (2022)
The intersections between economics and politics are not a new object in Political Science, especially in discussions about campaign finance. The empirical literature on electoral investment in Brazil, however, has devoted little attention to understanding the dynamics of campaign resources at the municipal level and the degree of participation of companies in local electoral processes. In the meantime, this work sought to verify the association between the participation of a certain economic sector in the municipal economy and the presence of business resources in electoral campaigns of local electoral processes. Thus, based on an empirical analysis of data on campaign finance for successful candidates in the 2008 and 2012 legislative elections in Bagé, Bento Gonçalves, Caxias do Sul, Rio Grande, Passo Fundo, Pelotas, Santa Cruz do Sul, Santa Maria and Uruguaiana, and economic data from these municipalities, mainly the sectorial composition of their municipal Gross Domestic Products (GDP), an attempt was made to answer the following question: how does the more expressive participation of an economic sector in the municipal economy affect the presence of a certain type of resource in the campaign of those elected to a Municipal Legislative? The proposed hypotheses drew, on the one hand, a positive association between industrial presence in the municipal GDP and the participation of corporate resources in campaigns and, on the other hand, a negative association between space occupied by the public sector in a municipal economy and corporate resources mobilized by elected candidates. Through an exploratory study - which mobilized techniques of a quantitative nature - it was possible to test the hypotheses suggested, to advance in the understanding of a neophyte theme and to point out trends to be objects of future works. In general, it is understood that the hypothesis was corroborated, whereas, both in the scenario in which the industrial sector stood out and in which emphasis was placed on public administration, the behavior expected by the financing data occurred. With the exception of two cases: Bento Gonçalves and Santa Cruz do Sul. In these two municipalities, despite the robust industrial sector and the significant participation of this sector in the GDP of the municipalities, there was no significant presence of legal entities in the financing of elected officials. A possible explanation for the anomalous behavior of these two cases is the interest of industries located in their limits in exporting their products, however, foreign trade policies are not a municipal responsibility.